Ã¢â‚¬ËœÃ¢â‚¬â„¢Langen Tayub Padang BulanÃ¢â‚¬Â As A Manifestation of Social and Cultural Change in Community - Juwariyah, Anik (Harmonia: Journal of Arts Research and Education, 2018)
This study examines Langen Tayub’s artistic position in social and cultural changes in society, especially in Nganjuk Regency. Langen Tayub as a product of a society that has undergone a change, also made innovations in Nganjuk community, this innovation was manifested in the form of a performance called Langen Tayub Padang Bulan. The research methods used include: Qualitative research approaches, data collection techniques uses: interviews, observation, documentation and recording. Data analysis used is the Talcott Parsons theory abbreviated as AGIL (A (adaptation), Achievement Goals (G-goal attainment), I (Integration), and L (latency) or pattern maintenance. Results showed that as a traditional cultural product, Langen Tayub experienced the changing form of presentation: Social and cultural changes that have taken place in the community have shifted the old model of Langen Tayub to Langen Tayub Padang Bulan, with some special characteristics that are adapted to the present conditions of society.